An Analysis of Translation Strategies of Idiom Translation in “Hotel Valhalla: Guide to The Norse Worlds” Companion Book - Kurniawan, Ricky Ilham (Syntax Corporation, 2025)
This study examines the translation strategies employed in the Indonesian version of Rick Riordan's